Prevalence of bovine dermatophilosis infaction and the associated factors in the communal area of Murehwa Zimbabwe - Munyanyi, Nyasha (Midlands State University, 2020)
A study to investigate the prevalence and associated risk factors was done in Murehwa district; Zimbabwe. The research was aimed at determining the prevalence of the disease and also determining the associated risk factors as determinants of the disease. The study was done by using questioners to randomly selected farmers who had reported the disease to the Veterinary Services. A total of 378 cattle were examined in the dry and the wet season. Statistical analysis was performed using SPSS version 20 software and Epi-info version 3 software. The findings reviewed no significant association of age (p=0.42); sex (p=0.863); presence of Amblyomma hebraeum (p=0.275); presence of the Rhepicaphalus tick species (p=0.834); dipping frequency and tick load whereas Amblyomma variegatum and season were statistically significantly associated with dermatophilosis with p values of p=0.000(p<0.05) and p=0.01(p<0.05) respectively. These results add to a growing body of evidence that, suggest the Amblyomma variegatum and season are strongly associated in the pathogenesis of dermatophilosis as highlighted by higher prevalence of dermatophilosis in the wet season (65.44%)95% CI( 56.81-73.8) as compared to the dry season (34.56%)95%CI (26.60-43.19). It is therefore strongly recommended that farmers use acaricides in controlling problematic ticks and also seasonal precautions to certain diseases should be done in order to control diseases which are more prevalent in wet seasons compared to dry seasons.